Brain-derived neurotrophic factor and nerve growth factor expression in endometriosis: A systematic review and meta-analysis - Danqiu Liu; Minjie Liu; Pinling Yu; Hongfeng Li (Taiwanese Journal of Obstetrics & Gynecology, 2023)
Endometriosis is diagnosed by laparoscopic surgery. The availability of biomarkers can help understand the pathophysiology and aid in the diagnosis of the condition. In this context, this review aimed to examine levels of expression of brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) are increased amongst patients with endometriosis and if they can serve as a potential biomarker. PubMed, CENTRAL, Scopus, Web of Science, and Embase databases were searched for studies comparing BDNF or NGF levels amongst endometriosis patients and controls. Data were pooled for serum and tissue levels of BDNF and NGF. Ten fulfilled the inclusion criteria. On comparing BDNF levels, it was noted that endometrial tissue had significantly higher expression of BDNF levels as compared to controls (SMD: 1.73 95% CI: 0.64, 2.82 I2 = 89%). Similarly, the meta-analysis found significantly higher serum levels of BDNF in endometriosis patients as compared to controls (SMD: 1.66 95% CI: 0.73, 2.59 I2 = 95%). Pooled analysis showed significantly increased levels of NGF in endometrial tissue as compared to controls (SMD: 4.15 95% CI: 0.11, 8.18 I2 = 98%) but with unstable results on sensitivity analysis. Only one study showed higher levels of NGF in serum amongst endometriosis patients. Limited data shows higher expression of BDNF in endometrial lesions and increased serum levels of BDNF in endometriosis patients. Similar results were noted for NGF but with very scarce data. Further research is needed to establish BDNF and NGF as suitable biomarkers for the disease.